Adherence to Recommendations from Comprehensive Geriatric Assessment of Older Individuals with HIV. (9th January 2019) - Bitas, Christiana; Jones, Sian; Singh, Harjot Kaur; Ramirez, Mildred; Siegler, Eugenia; Glesby, Marshall
This retrospective cohort study sought to assess the effectiveness of comprehensive geriatric assessment (CGA) for older patients at an HIV clinic in a large US city. We systematically reviewed medical records of all patients who underwent CGA from June 2013 to July 2017. In addition, physicians and social workers completed an anonymous survey about the impact of CGA on their patients. For the 76 patients (median age 67.2; Q1, Q3 = 60.9, 72.6) seen by geriatricians at the clinic, there were 184 recommendations, 54 instances of counseling, and 11 direct actions. Overall adherence to recommendations was 32.8%, 34.9% for patient-directed, and 31.7% for provider-directed recommendations. No demographic or CGA variables were associated with adherence. Despite this lack of adherence, surveyed providers reported that they usually or always followed recommendations; the most frequently cited barrier to implementation was lack of feasibility. Further research will be needed to determine how CGA can improve outcomes for this population.